Effect of shelter system on environmental variables* - SHARMA, PURUSHOTTAM; SINGH, KIRAN (The Indian Journal of Animal Sciences, 2014)
The study was conducted from March 1998 to February 1999 to investigate the effect of shelter system on environmental variables in diff’ercnl months. The trcatments were loose housing (control), loose housing with central shed and closed housing. In loose housing higher minimum temperature was observed in August (25.00 Â°C), while in closed housing it was higher in March, July to Sep, Nov to Jan i.e., 12.25, 27.25, 26.50, 25.60, 16, 25, 11.00 and 12.00Â°C respectively. The maximum temperature was higher in loose housing in Mar, April, July, Sep, Nov and Feb i.e .. 31.00, 43.25, 43,25,43.60, 33.50 and 31.00 Â°C respectively. Temperature, THI and vapour pressure were minimum in loose housing with central shed in most of the months.